ДІЯЛЬНІСТЬ ЮНЕСКО В СФЕРІ НАУКИ. - Пількевич, В. О. (Hileya: Scientific Bulletin / Gileya, 2018)
The activities of UNESCO (United Nations Educational, Scientific and Cultural Organization) in scientific field are researched. Science is one of the important directions of UNESCO. In the articles the author studies main programs «Man and Biosphere» (MAB), Intergovernmental Oceanographic Commission (IOC), International Hydrological Program (IHP), International Basic Sciences Programme, etc. Special attention was given combining different directions of activities of the Organization for obtaining greater results in preserving the natural heritage. Actual problem which is connected with the scientific sphere are analysed. United Nations Educational, Scientific and Cultural Organization organizes different conferences for solution problems of scientific field, gives important recommendation for improvements this sphere. The author emphasizes on importance involving information and communication technologies and new achievements in the scientific sphere for our future.